Flow start-up and transportation of waxy crude oil in pipelines-A review - Chala, G.T. (Elsevier B.V., 2018)
Wax deposition and gel formation have been crucial problems to the oil industries. The deposition of waxes would lead to gelation which blocks flow in pipelines and interrupts steady production of oil at offshore fields. The plugged gel needs to be restarted by applying a pressure that is much higher than the steady pressure in normal production flow, requesting for higher capacity pumps and piping dimensions. However, the available conventional restart pressure over-predicts pumping pressure and pipeline dimensions as it neglects the occurrence of thermal shrinkage and the resulting gas voids formed within the gelled crude oil and assumes waxy crude as single phase and incompressible fluid. The paucity of researches on quantification and locating of voids within the gel across and along the pipelines maintains the assumption made earlier to this date. There have been different researches conducted to prove that the over predicted restart pressure and piping dimensions result in excessive unnecessary cost to oil industries. This paper reviews the transportation of waxy crude oil at offshore fields and the previous researches on the behavior of waxy crude oil in Newtonian and non-Newtonian regions. In addition, the restart-ups process and the associated problems encountered, flow assurance and management of waxy crude oil, flow improvers of waxy crude oil gel following sufficient cooling are thoroughly discussed. It further reviews previous researches on thermal shrinkage and intra-gel voids formation in waxy crude oil which would help in the process of developing vigorous wax deposition model and restart pressure equations. Furthermore, different mechanisms used to ease restart pumping of gelled crude oil in pipelines are highlighted. Â© 2017 Elsevier B.V.